2019
DOI: 10.1177/1357633x19887262
|View full text |Cite
|
Sign up to set email alerts
|

Patient portal message characteristics and reported thoughts of self-harm and suicide: A retrospective cohort study

Abstract: Introduction As use of electronic portal communication with healthcare teams increases, processes that effectively recognize messages that contain critical information are needed. This study aims to evaluate whether certain language and other characteristics of patient portal messages are associated with expressions of self-harm and suicidal ideation. Methods Using patient portal messages sent between 1 January 2013 and 30 June 2017, we searched for words and letter combinations ‘suicid’ (to identify words sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Research on patient-generated content has primarily focused on online comments made by patients [20,49,50]. For instance, Chen and Baird [20] examined the impact of language signals in posts, including emotional valence, language style matching, readability, post length, and spelling, on the amount of social support patients receive.…”
Section: Literature Review 21 User-generated Content In Online Health...mentioning
confidence: 99%
See 1 more Smart Citation
“…Research on patient-generated content has primarily focused on online comments made by patients [20,49,50]. For instance, Chen and Baird [20] examined the impact of language signals in posts, including emotional valence, language style matching, readability, post length, and spelling, on the amount of social support patients receive.…”
Section: Literature Review 21 User-generated Content In Online Health...mentioning
confidence: 99%
“…This indicates that the consensus of other patients on treatment experiences can influence a patient's perception of treatment outcomes [49], validating the idea that the perceived effectiveness of a treatment is closely related to the perception of community participants about the treatment. Additionally, certain types of language and other features of patients on medical portal websites may be associated with user behavior [50]. Prior work has also further discovered that the narrative authenticity and coherence of user texts can impact user decision-making behavior [51].…”
Section: Literature Review 21 User-generated Content In Online Health...mentioning
confidence: 99%
“… 41 Studies have shown that adult patients may send messages that may be urgent including concerns for suicidality. 42 Patients may expect immediate response to patient portal messages, 29 but clinicians may have policies in place that give them up to 2 days to respond. 43 Patients must also understand a practice's approach to message workflow; for example, a message that they send to their physician may first be read and possibly completely managed by a nurse or administrator.…”
Section: Risks Of Portal Usementioning
confidence: 99%
“…11 However, this does not mean urgent and non-routine issues never appear in message content. Urgent issues may include high-risk symptomology, such as chest pain or breathing concerns, 12 self-harm or suicidality, 13 and other unresolved or urgent medical issues. 14 This may imply that providers need and do follow-up with patients in ways that extend beyond in-person appointments.…”
Section: Introductionmentioning
confidence: 99%